Sistema experto para diagnóstico de plagas insectiles de maíz (Zea mays L.) en Centro América - Merino Cisneros, Francisco Leopoldo (2016)
An expert system was developed to diagnose maize insect pests in Central America. This system was established ta improve diagnostic procedures for insect pests and to facilitate the use of integrated pest management systems in maize. This work was based on acquired knowledge by experts in integrated pest management based at the Centro Agronómico Tropical de Investigación y Enseñanza (CATIE). A shell expert system specific for diagnostics was used. This expert system is capable of diagnosing 52 maize insects usingsix inference modules. Criterion used were: plant phenology, damaged organ ofthe plant, general form of the insect, specific form of the insect, general damage, specific damage, and order and family of the insecto In addition, this systemcan provide information on insectsynonyms, common names, life cycle, damage, pest location, and possible control. The system works with IBM compatible MS-DOS, employs the VP-EXPERT shell, requires 512Kb of RAM, and either two 360 Kb or one 720Kb disk drives, or a hard disk. An evaluation ofthe ease of use of the shell dedicated to diagnostics for insect pests was performed. The purpose was to compare the educationallevel of the user with the ease which the shell was used. A completely randomized design was employed with seven treatments and five observations. The treatments were: secretaries, laboratory support staff, extension agents, bachelor level personnel, M.S., and PhD. level persons. Tbe results indicated that no significant differences within the range evaluated, excluding facility of use. It was concluded that the shell presents operationalilty that can be used by various persons at different education le veis within the studied rangc. expert system was also compared with a book key (‘Las plagas invertebradas de cultivos anuales alimenticios en America Central’). A randomized complete block design was used with two treatments and 18 replications, each replication being one persono The results dcmonstrated that the expert system was superior to the book key and that the expcrt system required much less time to obtain an answer.